Compositional variations in Ohm ray crater on the farside of the Moon: Implications for mafic anomaly. (May 2023) - Patel, Shreekumari; Satyakumar, A.V.; El-Maarry, M.R.; Solanki, Paras
Abstract: Ohm crater is a complex impact crater with a diameter of 64 ​km, placed on the northern side of the lunar farside. In this study, we derived Spectral Parameter maps, FeO and TiO2 abundance maps to infer the composition. Spectral analyses of M 3 data reveal presences of mafic minerals: Orthopyroxene and Clinopyroxene within the Ohm crater. A geostatistical technique is used to optimize the variation trend of diagnostic characteristics in different sites. We noticed that the western portion of Ohm is dominated by Cpx, whereas the rest of the crater is dominated by Opx. Cpx signifies impact melt crystallization of an anorthositic target crust, whereas Opx represents sources from the above and/or below the crust-mantle boundary. Negative gravity anomalies around the Ohm crater have been discovered by the NASA's dedicated mission, GRAIL, which could show a thicker crust underlying the crater. Around the Ohm crater, unequal Bouguer gravity anomalies and negative anomalies have been detected, however they are either absent or not clearly associated with internal morphology. These unequal gravity anomalies are entirely unconnected to surface morphological features. Furthermore, the Bouguer gravity signature may be influenced by pre-existing subsurface density structure as well as post-impact events (e.g., magmatism), resulting in some of the observed scatter. Low values in Ohm crater are likewise indicated by the regional gravity anomaly, implying that the thicker crust and cause of the geochemical abnormalities are at deeper levels. The predicted residual gravity anomalies show strong negative anomalies near Ohm crater, implying low density bodies at the crustal level. Based on regional and residual gravity anomalies, as well as compositional and mineralogical features of the Ohm crater, we suggest that the pyroxenes are the result of impact melt crystallization. When examining the mafic mineral distribution across the crater, another factor to examine is ejecta from the SPA, Orientale and mascon Hertzsprung basin, which may or may not have differed from impact melt formed during the Ohm impact event. Ohm crater's GRAIL crustal thickness model-1 indicates a thicker crust, confirming that the cause of the geochemical anomalies in this location is not the mantle upliftment. Graphical abstract: Image 1 Highlights: The compositional and spectral investigation carried out at Ohm crater, farside of the Moon. Our investigation shows mafic minerals of Orthopyroxene and Clinopyroxene present in the Ohm crater. The negative gravity anomalies and thickened crust indicate the source is at the lower crust/upper mantle.